2012
DOI: 10.1186/1756-0500-5-58
|View full text |Cite
|
Sign up to set email alerts
|

Clinically important improvement in the WOMAC and predictor factors for response to non-specific non-steroidal anti-inflammatory drugs in osteoarthritic patients: a prospective study

Abstract: BackgroundThe aims of the present study were first to detect MCID for WOMAC in a Moroccan population, and second, to identify the best pre-treatment predictors on the change of health after treatment by non-specific, non-steroidal anti-inflammatory drugs (NSAIDs), and to evaluate whether the predictors were dependent on the choice of the response criterion.MethodsThe study involved 173 patients with osteoarthritis in whom primary care physicians decided to start treatment with non-selective NSAIDs. Assessments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 28 publications
1
45
0
1
Order By: Relevance
“…This is consistent with what others have reported in the literature [1,2,5,7,8,18]. In this study, we found the group with the CPM to have a worse WOMAC score preoperatively, but the difference between the two groups is well below what has been established as the minimal clinically important difference [11]. No clinical important differences were found in WOMAC score.…”
Section: Discussionsupporting
confidence: 94%
“…This is consistent with what others have reported in the literature [1,2,5,7,8,18]. In this study, we found the group with the CPM to have a worse WOMAC score preoperatively, but the difference between the two groups is well below what has been established as the minimal clinically important difference [11]. No clinical important differences were found in WOMAC score.…”
Section: Discussionsupporting
confidence: 94%
“…At two weeks following TKA, WOMAC scores improved by an average of 46% compared to before surgery, with five of seven subjects (71%) achieving a clinically significant improvement of ≥33%. By 12 weeks following surgery, the average improvement relative to before surgery was 85%, and all seven subjects (100%) had achieved clinically significant improvements in WOMAC .…”
Section: Resultsmentioning
confidence: 94%
“…Changes of 20–25% in the WOMAC score are considered to be clinically relevant [35], but the most recent study suggested that a 16–18% reduction in the WOMAC score is associated with the MCID and should be appropriate for use in the interpretation of clinical studies, as well as in clinical care [36]. Our results indicate that a reduction of 32.2–36.4% from baseline was greater than the MCID of 16–18% or 20–25%, which suggests that TC has beneficial effects on pain, stiffness, and physical function in patients with knee OA.…”
Section: Discussionmentioning
confidence: 99%